Drift of invariant manifolds and transient chaos in memristor Chua's circuit - Mauro Di Marco; Mauro Forti; Luca Pancioni; Alberto Tesi (Electronics Letters, 2023)
Abstract The article shows that transient chaos phenomena can be observed in a generalized memristor Chua's circuit where a nonlinear resistor is introduced to better model the real memristor behaviour. The flux‐charge analysis method is used to explain the origin of transient chaos, that is attributed to the drift of the index of the memristor circuit invariant manifolds caused by the charge flowing into the nonlinear resistor.